Mastering environmental economics through an interactive Massive Open Online Course (MOOC) for optimal online learning - Hammad Ahmad Khan, Hafizah; Ahmad, Nabila; Mohd Sidek, Noor Zahirah; Othman, Muhammad Hanif; Ahmad Fuad, Hanani (Universiti Teknologi MARA, Kedah, 2023)
In today's world, environmental challenges are at the forefront of global concerns. Understanding the link between economics and the environment is crucial for sustainable development. Therefore, to address this critical need, this project is being developed to offer an interactive and engaging Massive Open Online Course (MOOC) aimed at empowering learners to grasp the principles of environmental economics. The primary objectives of this MOOC are threefold. Firstly, it seeks to explain key concepts and theories of environmental economics, wherein learners will delve into the core principles governing the relationship between economic activities and environmental impacts, gaininginsights intothe balance between growth and environmental goals. Secondly, the course aims to integrate social responsibility with elements of environmental economics for the wellness of the community. By emphasizing the importance of social and environmental welfare, learners will explore how economicdecisions can be shaped to foster equitable and sustainable outcomes for society and the environment. Thirdly, the MOOC aims to analyze environmental issues and problems using relevant theories and concepts of environmental economics. The content, developed based on the Gagne 9 event theory, is beneficial for enhancing online learning and promoting active participation among learners, contributing to a more informed and environmentally conscious global community.